A Review of Process Monitoring Method and Rule Extraction Method for Manufacturing Process Quality Control (International Journal of Computer Science and Information Technology, 2024)
Nowadays, scholars have explored many methods for manufacturing process quality control. This paper presents the current research progress in these two areas in manufacturing process quality control by exploring the two areas of process monitoring and rule extraction, and analyzes the strengths and weaknesses of the current research. In the review of process monitoring, the paper introduces a variety of research methods based on different data characteristics of the manufacturing process, which makes the differentiation of different data characteristics and the applicability of the methods more obvious. In the research review on rule extraction, this paper will introduce the characteristics of excellent rule extraction algorithms and introduce various rule extraction algorithms and their applications. Finally, this paper expects to combine the two to put forward some suggestions on future research directions.